Intrinsic Surface‐Drying Properties of Bioadhesive Proteins1. (28th August 2014) - Akdogan, Yasar; Wei, Wei; Huang, Kuo‐Ying; Kageyama, Yoshiyuki; Danner, Eric W.; Miller, Dusty R.; Martinez Rodriguez, Nadine R.; Waite, J. Herbert; Han, Songi
Abstract Sessile marine mussels must "dry" underwater surfaces before adhering to them. Synthetic adhesives have yet to overcome this fundamental challenge. Previous studies of bioinspired adhesion have largely been performed under applied compressive forces, but such studies are poor predictors of the ability of an adhesive to spontaneously penetrate surface hydration layers. In a force‐free approach to measuring molecular‐level interaction through surface‐water diffusivity, different mussel foot proteins were found to have different abilities to evict hydration layers from surfaces—a necessary step for adsorption and adhesion. It was anticipated that DOPA would mediate dehydration owing to its efficacy in bioinspired wet adhesion. Instead, hydrophobic side chains were found to be a critical component for protein–surface intimacy. This direct measurement of interfacial water dynamics during force‐free adsorptive interactions at solid surfaces offers guidance for the engineering of wet adhesives and coatings.